Infection of the gibel carp (Carassius auratus gibelio Berg, 1932) with myxozoan parasites in a pond farm of Hungary - Nadhirah Syafiqah Suhaimi; Gábor Cech; Kálmán Molnár; Csaba Székely; Boglárka Sellyei (Aquaculture Reports)
Previously, only two myxozoan species have been reported from gibel carp in Hungary, compared to over 40 myxozoan parasites described in China. Due to their invasive nature and limited economic importance in Hungary, parasitological examinations of this fish species have often been overlooked. In this study, a comprehensive parasitology survey was conducted, revealing six myxozoan parasites, including three different Myxobolus spp., one Thelohanellus sp., one Sphaerospora sp., and one Zschokkella sp. infected various organs and tissues. Based on the morphological and molecular data, we described four new species: Myxobolus ocsardiensis n. sp., found in the kidney and liver; Myxobolus pecsensis n. sp., found in the gill cartilage; Thelohanellus imrei n. sp. found in the connective tissues of the gill arch and pharynx; and Zschokkella chezhachei n. sp. found in the bile duct. Additionally, we identified spores resembling those of Myxobolus diversus, a parasite of the fins of goldfish, and Sphaerospora molnari known from the gills of crucian carp and common carp. The original description of these species lacked several important information such as spore measurements and molecular data, requiring their redescription. Here, we redescribed M. diversus and S. molnari based on spore measurements, molecular data and histological comparisons, marking their first report in gibel carp. Phylogenetic analyses indicated the six species clustered into distinct monophyletic clades consisting of Myxobolus, Thelohanellus, Sphaerospora and Zschokkella clades.